PERAN PENDIDIKAN NON FORMAL UNTUK MEMBANTU SISWA DROP OUT DALAM MENYELESAIKAN SEKOLAHNYA - Probo Astikaningtyas; Abdul Rahman; Yosafat Hermawan Trinugraha (STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
This study aims to find out the strategies adopted by non-formal educational institutions in developing educational programs for dropout students, as well as to find out what are the supporting and inhibiting factors in developing educational programs for school dropouts. This study uses a case study research design with qualitative research methods. The data collection through observation, interviews, and documentation. The validity of the data was tested using source triangulation. Test the validity of the data using an interactive analysis model from Miles & Hubbermas through the stages of data reduction, data presentation, and drawing conclusions. From this study, it is known that PPAP Seroja non-formal educational institutions have several strategies in developing educational programs for dropout students, namely, especially affordable education costs and facilities for underprivileged students. In the process there are several obstacles faced, especially the low enthusiasm of students to learn. The success of the development of non-formal education is supported by several factors, but the most influential factor is the presence of volunteers as educators or teachers.